Prospects for the use of digital technologies in education - Nilufar Khalikova Mirkadirovna (Open Academia, 2023)
The integration of digital technologies in education has transformed traditional teaching methods, offering new opportunities for both educators and learners. This article explores the current landscape of digital technologies in education, analyzing existing literature, discussing various methods employed, presenting results, and drawing conclusions for future implications. With a focus on the advantages and challenges associated with these technologies, this article aims to provide insights into the evolving role of digital tools in shaping the future of education.
Keywords: Digital technologies; Education; EdTech